INFLUENCE OF NATURE AND CONCENTRATION OF VARIOUS FILLERS FOR FLEXIBLE EMR SHIELDS UPON THEIR SHEILDING CHARACTERISTICS IN SHF BAND: I. SOLUTIONS OF ACIDS AND POTASSIUM SALTS - S. V. Halushka; M. Ali Alhamruni; N. V. Nasonova; А. А. Poznyak (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The effectiveness characteristics of flexible shielding materials based on textile matrixes impregnated with aqueous solutions of organic acids, boric acid and potassium salts of various concentration in the frequency bands 8-11 и 27-36 GHz are studied. Diluted solutions (0,1 М) of acids and salts slightly differ from distilled water as the EMR suppression is produced due to high dielectric losses of water. The smallest transmission coefficient was obtained for the sample with a 1 М solution of potassium ferricyanide (III) - down to minus 17,8 dB in the frequency band of 8-11 GHz and down to minus 31 dB in the frequency band of 27-36 GHz because of its high reflective properties.